Working with families in children's centres and early years settings - Whalley, Margy; Orr, Robert; Arnold, Cath (Hodder Education, 2013)
This textbook, published in partnership with the internationally renowned Pen Green Centre, based in Corby, UK, will give you an accessible overview of the most current research into working with families and how this can be applied for Children's Centres and Early Years settings, whether you are a foundation degree or undergraduate learner, or a professional working in an early years setting.--Publisher's website.